A multi-level analysis of prevalence and factors associated with caesarean section in Nigeria - Kobi V. Ajayi; Samson Olowolaju; Yusuf H. Wada; Sonya Panjwani; Bright Ahinkorah; Abdul-Aziz Seidu; Collins Adu; Olajumoke Tunji-Adepoju; Obasanjo Afolabi Bolarinwa (Public Library of Science (PLoS), 2023)
The choice of caesarean section (CS) plays a significant role in maternal and neonatal health. However, suboptimal CS uptake suggests unmet obstetric care leading to adverse maternal and neonatal health. Considering that maternal health problems in Nigeria remain a public health problem, this present study aims to assess the prevalence and multilevel factors associated with caesarean section among women of reproductive age in Nigeria. Data from the 2018 Nigeria Demographic and Health Survey were analysed. Our analyses included 19,964 women of reproductive age, with their last birth within five years preceding the survey. Multilevel logistic regression analysis was carried out to examine the predictors of the caesarean section in Nigeria. The prevalence of CS among women of reproductive age in Nigeria was 3.11%. Women from the Yoruba ethnic group [aOR = 0.52; 95%(CI = (0.32-0.84)], with two children [aOR = 0.67; 95%(CI = 0.52-0.88)], three children [aOR = 0.49; 95%(CI = 0.36-0.66)], four children and above [aOR = 0.34; 95%(CI = 0.26-0.46)], those who practised Islam [aOR = 0.74; 95%(CI = (0.56-0.99)], and those that had a normal weighted baby [aOR = 0.73; 95%(CI = 0.60-0.99)] were less likely to report having a CS in Nigeria compared to those from Hausa/Fulani ethnic group, those who had one child, those who practised Christianity, and those who had a high weighted baby. Also, women residing in rural areas [aOR = 0.79; 95% (CI = (0.63-0.99)] and the South-South [aOR = 0.65; 95%(CI = (0.46-0.92)] were less likely to have CS compared to those residing in urban areas and North Central. The study concluded that several individual and community-level factors, such as religious belief, number of children, ethnicity, place of residence, and region of residence, were associated with CS utilisation in Nigeria. Our study highlights the need for different regional, local, and cultural contexts for evidence-based policy and programmatic efforts to facilitate equitable access to a caesarean section in Nigeria.